Isolated superfused rats atrial model for the investigation of atrial fibrillation mechanisms and treatment. (14th October 2021) - Glatstein, S; Ghiringhelli, M; Maizels, L; Heller, E; Maor, E; Gepstein, L
Abstract: Background: One of the major barriers to an improved mechanistic understanding of atrial fibrillation (AF), and thus in the pipeline of drug development, has been a lack of appropriate tissue models, especially in small animals. Aim: We propose an advanced anatomical ex-vivo model based on rat atria for acute assessment of AF susceptibility. This novel model could yield a better understanding of arrhythmia mechanisms as well as the development of potential therapeutic strategies for the prevention or termination of atrial arrhythmias. Methods: Wistar rats atria (N=25) were isolated, flattened and pinned to a custom-made silicon plate. Atria were superfused with an oxygenized Tyrode's solution. Tissues were then loaded with a voltage-sensitive dye and mapped using a high-resolution optical mapping system. AF was induced with 1uM carbamylcholine (N=23) coupled with pacing maneuvers and treated with 30uM Vernakalant (N=10) or 10uM Flecainide (N=10). Finally, the feasibility of a new ablation technique (electroporation) was evaluated. Results: Optical mapping results suggested that the superfusion procedure led to a fast atrial recovery. Sinus activity was conserved for all atria for a long period. All the anatomical landmarks were clearly visualized. The acquired optical signals were analyzed during sinus rhythm and pacing, which allowed the creation of detailed activation maps and measurements of action potential duration (APD) and conduction velocity (CV) at different pacing rates. The resulting APD restitution curves revealed electrical excitation at high pacing rates (cycle length between 50ms and 300ms) with a relatively flattened curve. AF was successfully induced and optically mapping confirmed the presence of reentrant activity. AF was successfully treated using Vernacalant and Flecainide. Finally, we demonstrated the feasibility of a new ablation approach (electroporation) for creation of a continuous linear lesion serving as a functional block. Conclusion: The isolated superfused atria model, coupled with voltage-sensitive dyes, can be utilized for long-term high-resolution functional imaging of the atria during sinus rhythm, pacing and arrhythmogenic activity. This allows the study of the atrial electrophysiological properties, the mechanisms involved in AF initiation, perpetuation, and termination as well as the study of drug and new ablation modalities. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Research Council (ERC)